Electronic properties of carbazole/biphenylamino functionalized sulfone‐based host materials. (14th January 2023) - Xu, Xiaopei; Huang, Zehua; Liang, Xuefeng; Tang, Xinyuan; Zhao, Yongze; Li, Huifang; He, Yan; Zhang, Lisheng
Abstract: Sulfone‐based molecules are widely used as molecular building blocks for host materials in the emissive layers of organic light‐emitting diodes (OLEDs). In this work, the electronic properties of dibenzo[b, d]thiophene 5, 5‐dioxide (DBTO) and its derivatives were investigated by quantum‐chemical techniques to get more detailed information about the carbazole and biphenylamino functionalization effects on the charge injection property and triplet transition energy of such SO2 ‐based host materials. Calculated results demonstrated that the charge injection property of DBTO can be tuned by different functionalization strategies. Vertical ionization potential (VIP) and vertical electron affinity (VEA) values are reduced by functionalization, especially in the case of biphenylamino substitution. The S0  → S1 and S0  → T1 * transitions, which are mainly dominated by the HOMO and LUMO energy levels, can also be tuned by functionalization. For the S0  → S1 transition, the effect of carbazole substitution is larger than that of biphenylamino substitution, while the effect of carbazole substitution on the S0  → T1 * transition energies of DBTO is smaller than that of biphenylamino substitution. This effect will be more obvious if the number of introduced functional groups increases. In addition, it was observed that the substitution effect at the meta ‐position of DBTO is much larger than that at the para ‐position. Abstract : The charge injecting property of sulfone‐based materials can be tuned by different functionalization strategy, and the VIP and VEA values will be lowered by functionalization especially for the substitution with biphenylamino group. For S0‐to‐S1 transition, the influence coming from carbazole substitution is larger than that from biphenylamino, but is smaller than that of tricarbazole. The carbazole substitution effects on the S0 to T1* and T1 to S0* transition energies of DPSO are much smaller than that from biphenylamino.